Prevalence of Burkholderia species, including members ofBurkholderia cepaciacomplex, among UK cystic and non‐cystic fibrosis patients. Issue 4 (April 2017) - Kenna, Dervla T. D; Lilley, Daniel; Coward, Amy; Martin, Kate; Perry, Claire; Pike, Rachel; Hill, Robert; Turton, Jane F
Abstract : Purpose. : We aimed to establish the prevalence of different Burkholderia species among UK cystic fibrosis (CF) and non‐CF patients over a 2 year period. Methodology. : Matrix‐assisted laser desorption/ionization‐time of flight mass spectrometry was used to identify isolates to genus level, followed by recA/gyrB sequence clustering or species‐specific PCR. In all, 1047 Burkholderia isolates were submitted for identification from 361 CF patients and 112 non‐CF patients, 25 from the hospital environment and three from a commercial company. Potential cross‐infection was assessed by pulsed‐field gel electrophoresis (PFGE) and multi‐ locus‐sequence typing (MLST). MICs were determined for 161 Burkholderia cepacia complex (Bcc) isolates. CF Trust registry data were sought to examine clinical parameters relating to Bcc infection. Results. : Burkholderia multivorans was the most prevalent species among CF patients affecting 56% (192) patients, followed by Burkholderia cenocepacia IIIA (15%; 52 patients). Five novel recA clusters were found. Among non‐CF patients, Burkholderia cepacia was the most prevalent species (37/112; 34%), with 18 of 40 isolates part of a UK‐wide B. cepacia 'cluster'. This and three other clusters were investigated by PFGE and MLST. Cable‐pili positive isolates included two novel sequence types and representatives of ET12. Antibiotic susceptibility varied between and within species and CF/non‐ CF isolates. CF Trust registry data suggested no significant difference in lung function between patients harbouring B. cenocepacia, B. multivorans and other Bcc species ( P =0.81). Conclusion. : The dominance of B. multivorans in CF, the presence of a B. cepacia cluster among non‐CF patients and the existence of putative novel species all highlighted the continuing role of Burkholderia species as opportunistic pathogens.